Minat Beli Konsumen Hidroponik : Ditinjau dari Green Product, Price dan Location di Muria Kudus - Karsono, Lorena Dara Putri; Salmaa, Khananus (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2023)
Raya Hidroponik Muria is trying to increase buying interest in its hydroponic vegetables, but in reality there are certain groups who have not reached hydroponic vegetable products because of a lack of awareness about the environment and health. In addition to the high price of hydroponic vegetables and production that is difficult to access, it is still a problem for consumers. The purpose of this research is to empirically interpret the effect of green product, price, location on consumer buying interest Raya Hydroponics Muria. The population in this study were consumers Raya Hydroponics Muria Kudus, with the technique used in sampling in the form of incidental sampling and using a convenience sampling approach because the population size was unknown, so that the sample in this study was obtained by 100 respondents. The type of research used is field research with a quantitative approach the hypothesis that has been carried out through multiple linear regression analysis using SPSS 21.0. The results show that product has an effect on consumer buying interest, price has an effect on consumer buying interest, location has an effect on consumer buying interest and green product, price, location together influence consumer buying interest in Raya Hydroponic Muria.